A new design strategy for redox-active molecular assemblies with crystalline porous structures for lithium-ion batteries. Issue 1 (29th November 2019) - Nakashima, Kensuke; Shimizu, Takeshi; Kamakura, Yoshinobu; Hinokimoto, Akira; Kitagawa, Yasutaka; Yoshikawa, Hirofumi; Tanaka, Daisuke
Abstract : A new design strategy for the high-performance organic cathode-active materials of lithium-ion batteries is presented, which involves the assembly of redox-active organic molecules with a crystalline porous structure. Abstract : A new design strategy for high-performance organic cathode active materials for lithium-ion batteries is presented, which involves the assembly of redox-active organic molecules with a crystalline porous structure using mixed-stacked charge-transfer (CT) complexes. Hexahydroxytriphenylene was used as a donor molecule and 1, 4, 5, 8, 9, 12-hexaazatriphenylene-2, 3, 6, 7, 10, 11-hexacarbonitrile as an acceptor molecule to give a new porous CT complex (PCT-1 ) with a pseudo-hexagonal mixed columnar structure. X-ray diffraction measurements and sorption experiments demonstrated that the intercolumnar spaces in PCT-1 can incorporate various molecules accompanied by lattice expansion. A lithium metal battery containing PCT-1 as a cathode active material exhibited a high capacity of 288 mA h g −1 at 500 mA g −1, and this performance was attributed to a combination of the redox-active units and the porous structure of PCT-1 .